1999
DOI: 10.1016/s0042-6989(98)00228-4
|View full text |Cite
|
Sign up to set email alerts
|

Saccades require focal attention and are facilitated by a short-term memory system

Abstract: We performed two sets of experiments in which observers were instructed to make saccades to an odd colored target embedded in an array of distractors. First, we found that when the colors of the target and distractors switched unpredictably from trial to trial (the mixed condition), saccadic latencies decreased with increasing numbers of distractors. In contrast, saccadic latencies were independent of the number of distractors when the color of the target and distractors remained the same on each trial (the bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
145
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(162 citation statements)
references
References 23 publications
17
145
0
Order By: Relevance
“…In a similar vein, the Bgaze reorientation^hypothesis argued by Maljkovic and Nakayama (1996) proposes that PoP and position-based priming (in a PoP task) depend on a representation in a Bshort-term memory,^which is the basis of reorienting eye gaze to an object or location involved in a sequence of actions. Later eye movement studies (McPeek, Maljkovic, & Nakayama, 1999) supported the gaze reorientation hypothesis by showing that saccades to a target were faster and more accurate when the target color was repeated across trials. This result indicates that the underlying mechanism of PoP is responsible for rapidly reorienting the observer's gaze to a recently foveated target.…”
Section: Discussionmentioning
confidence: 93%
“…In a similar vein, the Bgaze reorientation^hypothesis argued by Maljkovic and Nakayama (1996) proposes that PoP and position-based priming (in a PoP task) depend on a representation in a Bshort-term memory,^which is the basis of reorienting eye gaze to an object or location involved in a sequence of actions. Later eye movement studies (McPeek, Maljkovic, & Nakayama, 1999) supported the gaze reorientation hypothesis by showing that saccades to a target were faster and more accurate when the target color was repeated across trials. This result indicates that the underlying mechanism of PoP is responsible for rapidly reorienting the observer's gaze to a recently foveated target.…”
Section: Discussionmentioning
confidence: 93%
“…shown that target feature changes indeed bias attention and the gaze to the nontargets (e.g., Becker, 2008aBecker, ,b,c, 2010aBecker, ,b, 2013McPeek, Maljkovic & Nakayama, 1999).…”
Section: Explaining Switch Costs At Feature and Dimension Changesmentioning
confidence: 99%
“…This two-system hypothesis is currently supported by three major findings. First, altering the target feature usually delays eye movements to the target (e.g., Becker, 2008aBecker, , b, c, 2013McPeek et al, 1999), whereas changing the target dimension does not interfere with selection of the target but rather prolongs target dwell times (e.g., Becker, 2010a). Second, electroencephalography (EEG) studies have found that swapping the target and non-target features leads to large delays in the onset of the N2pc (~50ms; Eimer, Kiss & Cheung, 2010), an electrophysiological marker for spatial attentional selection (e.g., Eimer, 1996;Luck & Hillyard, 1994), whereas dimension changes have only small effects on N2pc latencies (~8ms; e.g., Töllner et al, 2008;6ms, Töllner et al, 2010, Rangelov et al, 2013 that cannot account for the substantial RT delay of 30-50ms.…”
Section: Introductionmentioning
confidence: 99%
“…The role of attention in saccadic eye movements has been studied extensively in head-restrained conditions. It has been established that saccade execution requires a shift of attention to the saccade goal (e.g., Deubel and Schneider 1996;Hoffman and Subramaniam 1995;Kowler et al 1995;McPeek et al 1999), indicating a close linkage between eye movements and attention. Such a linkage is also supported by a number of studies showing shared neural substrates for saccadic eye movement planning and attentional processing (e.g., Beauchamp et al 2001;Cavanaugh and Wurtz 2004;Corbetta et al 1998;Goldberg et al 2006;Ignashchenkova et al 2004;Kastner and Ungerleider 2000;Moore and Fallah 2001;Muller et al 2005; Thompson et al 2005).…”
Section: Introductionmentioning
confidence: 99%